Polypyrrole / cellulose gel with anisotropic structure as well as preparation method and application of polypyrrole / cellulose gel

By preparing anisotropic polypyrrole/cellulose gels with anisotropic structures in water evaporation materials, using pre-stretching and vapor deposition technology, the problems of low energy utilization and insufficient thermal management capabilities of existing water evaporation materials are solved, and efficient photothermal conversion and power generation performance are achieved.

CN119529372APending Publication Date: 2025-02-28NAT ENERGY GRP LEDONG POWER GENERATION CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411853005.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing water evaporation materials have low energy utilization during water evaporation, and the isotropic hydrogels have shortcomings in thermal management and ion transport capabilities.

Method used

Cellulose hydrogels were prepared by microcrystalline cellulose and alkali urea systems, and the cellulose chain structure was controlled in a directionally to form an anisotropic structure. Polypyrroles are then grown on the cellulose hydrogel surface by vapor deposition to form a continuous charged nanochannel.

Benefits of technology

It realizes excellent photothermal conversion and power generation capabilities of polypyrrole/cellulose gel under the dual driving of water and thermal gradients, and has efficient thermal management performance and fast ion transmission capabilities, which can provide a new way to extract energy from natural resource water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529372A_ABST
    Figure CN119529372A_ABST
Patent Text Reader

Abstract

The invention provides polypyrrole / cellulose gel with an anisotropic structure as well as a preparation method and application thereof, and the preparation method of the polypyrrole / cellulose gel comprises the following steps: S1, adding sodium hydroxide and urea into water to obtain an alkali urea solution; s2, adding microcrystalline cellulose into an alkali urea solution, carrying out ultrasonic treatment, and repeatedly freezing and thawing to obtain a cellulose solution; s3, adding an epichlorohydrin cross-linking agent into the cellulose solution, stirring, centrifuging, and gelatinizing at low temperature to obtain pre-loose cross-linked gel; s4, pre-stretching the pre-loose cross-linked gel for a certain length, and immersing the pre-loose cross-linked gel into a dilute sulfuric acid solution to form anisotropic cellulose hydrogel with different orientation degrees; s5, the cellulose hydrogel is soaked in an ammonium persulfate solution and taken out, pyrrole is added for polymerization growth, freeze drying is conducted, aerogel is formed, and the cellulose aerogel is obtained. The cellulose hydrogel provided by the invention has excellent water evaporation and ion output capabilities, and also has excellent thermal management performance and power generation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of water treatment and energy utilization, and in particular to a polypyrrole / cellulose gel with an anisotropic structure and a preparation method and application thereof. Background Art

[0002] The demand for electricity and fresh water is always intertwined. With the rapid population growth and environmental pollution, the issue of fresh water and electricity faces huge challenges. Solar thermal interfacial evaporation technology is one of the most promising water purification technologies. By further utilizing the energy in interfacial evaporation technology, an efficient water-electricity cogeneration model can be established.

[0003] In recent years, various excellent photothermal conversion materials, such as semiconductors, carbon materials, metal nanoparticles, etc., have been widely used in solar photothermal interface evaporation. However, the further utilization of energy is often ignored in the process of water evaporation, resulting in energy loss in the form of reflection, conduction, etc. Therefore, efficient utilization of energy is crucial for evaporators.

[0004] Traditional water evaporation materials have the problem of low thermal management and energy utilization. As one of the best photothermal interface evaporation materials at present, the three-dimensional network structure of hydrogel gives hydrogel excellent water transmission ability. For example, patent CN111518309A discloses a biomass nanocellulose / polypyrrole composite aerogel and its preparation method and application, which prepares cellulose hydrogel with biomass material and ammonium persulfate, and then soaks it in a phytic acid solution of pyrrole, freeze-dries it, and obtains cellulose / polypyrrole composite aerogel. The water absorption of the biomass nanocellulose network structure and the electrical conductivity and heat absorption properties of polypyrrole are utilized, but the hydrogel obtained by this method is an isotropic structure, and the thermal management and low ion transmission capabilities are slightly poor and unstable.

[0005] Compared with the isotropic structure, the anisotropic structure has excellent thermal management performance and fast ion transmission ability. For example, patent CN108409997A discloses a method for preparing an ultra-high strength anisotropic hydrogel containing cellulose nanowhiskers, in which a single cross-linked hydrogel physically cross-linked with cellulose nanowhiskers is prepared by host-guest interaction, and before the secondary cross-linking, the single cross-linked hydrogel is pre-stretched and oriented by external force, and Fe is added. 3+ Secondary cross-linking can fix the orientation of cellulose nanowhiskers in the network. The anisotropic hydrogel produced by this patent exhibits excellent mechanical properties. The preparation method is relatively complicated, and the thermal management performance and ion transmission capacity have not been studied, so its effect is unknown. Summary of the invention

[0006] In view of this, the present invention proposes a polypyrrole / cellulose gel with an anisotropic structure and a preparation method and application thereof. The preparation method is simple and can regulate the orientation of cellulose molecular chains. The obtained polypyrrole / cellulose gel has an anisotropic structure and has excellent photothermal conversion and power generation capabilities.

[0007] The technical solution of the present invention is achieved in this way:

[0008] A method for preparing anisotropic polypyrrole / cellulose gel, the specific steps comprising:

[0009] S1, adding sodium hydroxide and urea into water to obtain an alkaline urea solution;

[0010] S2, adding microcrystalline cellulose to the alkaline urea solution of S1, ultrasonically treating, and repeatedly freezing and thawing to obtain a cellulose solution;

[0011] S3, adding epichlorohydrin crosslinking agent to the cellulose solution in S2, stirring, centrifuging, and gelling at low temperature to obtain a pre-loose crosslinked gel;

[0012] S4, pre-stretching the pre-loose cross-linked gel of S3 to a length of 0%-160% and then immersing it in a dilute sulfuric acid solution to react, thereby forming anisotropic cellulose hydrogels with different orientation degrees; further, the pre-stretching lengths are 0%, 80% and 160%;

[0013] S5. Soak the cellulose hydrogel of S4 in an ammonium persulfate solution, take it out, add pyrrole for polymerization growth, and freeze-dry to form an aerogel, i.e., a polypyrrole / cellulose gel with an anisotropic structure.

[0014] Furthermore, in step S1, the mass ratio of the sodium hydroxide to urea is 1:1.5-2.5; the solid-liquid ratio of the sodium hydroxide to water is 1:11-13 g / mL.

[0015] Furthermore, in step S2, the solid-liquid ratio of the microcrystalline cellulose to the alkaline urea solution is 1:10-20 g / mL; and the ultrasonic treatment is performed at 500-1000 rpm and 25-30° C. for 10-20 min.

[0016] Furthermore, in step S2, the repeated freeze-thaw is specifically as follows: first freezing at -20°C for 12-14 hours, taking out, stirring in an ice bath for 30-60 minutes, and repeating the above process 2-3 times.

[0017] Furthermore, in step S3, the mass ratio of the epichlorohydrin crosslinking agent to the cellulose solution is 1.5-1.6:50; the stirring treatment is carried out at a temperature of -5 to 0°C, a rotation speed of 1000-1500 rpm, and a time of 2-4 hours.

[0018] Furthermore, in step S3, the low-temperature gelling is carried out by placing the mixture at 5-10° C. for 8-10 hours.

[0019] Furthermore, in step S4, the concentration of the dilute sulfuric acid solution is 5-8 wt %; and the reaction time is 1-2 min.

[0020] Immersed in a dilute sulfuric acid solution for acid-base neutralization reaction, sulfuric acid can destroy the alkaline urea inclusion complex wrapped around the cellulose molecular chains, exposing the cellulose molecular chains. The hydrogen bonds between the exposed cellulose molecular chains interact to produce physical cross-linking, thereby forming a permanently oriented cellulose hydrogel.

[0021] Furthermore, in step S5, the concentration of the ammonium persulfate solution is 2-10wt%; the immersion time is 1-3h; the specific process of the pyrrole polymerization growth is: firstly polymerize and grow at room temperature for 20-24h, wash with water, freeze at -20°C for 12-24h, remove the surface layer, continue to immerse in the ammonium persulfate solution for 1-2h, freeze at -20°C for 12-24h, take out after freeze drying, and polymerize and grow at room temperature for 4-6h.

[0022] A polypyrrole / cellulose gel with an anisotropic structure is prepared by any of the above-mentioned preparation methods.

[0023] Application of anisotropic polypyrrole / cellulose gel in the field of solar desalination and electricity utilization.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention prepares cellulose hydrogel by microcrystalline cellulose and alkali urea system, and adopts pre-stretching strategy to directionally control the structure of cellulose chain in chemical gel state, which can make full use of the energy generated in the evaporation process, reduce heat loss, and form a tight physical network through the strong self-aggregation force between adjacent cellulose nanofibers, presenting a highly ordered nanostructure. Then, polypyrrole is grown on the surface of anisotropic cellulose hydrogel by vapor deposition, uniformly deposited, and rich continuous charged nanochannels are formed to play the role of rapid ion transmission. Under the dual drive of water and thermal gradient, the anisotropic cellulose hydrogel of the present invention has excellent water evaporation and ion output capacity under sunlight, providing a new way to extract energy from natural resource water. At the same time, it has excellent thermal management performance and power generation performance. The anisotropic cellulose hydrogel of the invention is negatively charged after potential testing. This experimental example verifies that multiple MCC@PPy-160% materials connected in series can provide power for LED devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1This is the SEM electron microscope image of the MCC@PPy-160% anisotropic polypyrrole / cellulose gel of Example 3.

[0027] Figure 2 This is the infrared spectrum of the anisotropic polypyrrole / cellulose gel of Example 3.

[0028] Figure 3 This is an infrared thermal image of the anisotropic polypyrrole / cellulose gel of Example 1-3.

[0029] Figure 4 Graph showing the heating rate of the anisotropic polypyrrole / cellulose gel of Examples 1-3.

[0030] Figure 5 Graph showing the water evaporation rate of the anisotropic polypyrrole / cellulose gel of Examples 1-3.

[0031] Figure 6 The open circuit voltage of the anisotropic polypyrrole / cellulose gel of Example 3 at different salt concentrations under dark conditions.

[0032] Figure 7 It is the open circuit voltage of the anisotropic polypyrrole / cellulose gel of Example 1-3 under dark conditions and a salt concentration of 1 mol / L.

[0033] Figure 8 The open circuit voltage of the anisotropic polypyrrole / cellulose gel of Example 3 at different salt concentrations under illumination conditions.

[0034] Fig. 9 The current of the anisotropic polypyrrole / cellulose gel of Example 3 at different salt concentrations under illumination conditions.

[0035] Fig.10 This is a graph of water evaporation rates of MCC@PPy-160% of Example 3 and MCC-160% of Comparative Example 1.

[0036] Fig.11 The open circuit voltage of MCC@PPy-160% of Example 3 and MCC-160% of Comparative Example 1 under dark conditions at a salt concentration of 1 mol / L.

[0037] Fig.12 This is a real picture of the total voltage of the MCC@PPy-160% series connection and the lit LED small colored lights in Example 3. DETAILED DESCRIPTION

[0038] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0039] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0040] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0041] The pre-stretching length in the present invention is 0%, and the polypyrrole / cellulose gel with an anisotropic structure finally formed is named MCC@PPy-0%; the pre-stretching length is 80%, and the polypyrrole / cellulose gel with an anisotropic structure finally formed is named MCC@PPy-80%; the pre-stretching length is 160%, and the polypyrrole / cellulose gel with an anisotropic structure finally formed is named MCC@PPy-160%.

[0042] The maximum pre-stretching length of the present invention is 160%. If the pre-stretching length exceeds 160%, the pre-stretching length will break. Therefore, the present invention does not study the length exceeding 160%.

[0043] Example 1

[0044] The method for preparing the anisotropic polypyrrole / cellulose gel of this embodiment specifically comprises the following steps:

[0045] S1. Weigh 7 g of sodium hydroxide and 12 g of urea, add into 81 mL of water, and prepare alkaline urea solution;

[0046] S2, weighing 6 g of microcrystalline cellulose, adding it to the above 15 mL of alkaline urea solution, ultrasonically treating it at 1000 rpm and 25° C. for 20 min, first freezing it at -20° C. for 12 h, taking it out, stirring it in an ice bath for 30 min, repeating the above freeze-thaw process 2-3 times to obtain a cellulose solution;

[0047] S3, take out 50g of cellulose solution, then add 1.6g of epichlorohydrin crosslinking agent, stir at 0℃, 1000rpm, for 4h, place in a centrifuge, centrifuge at 6000rpm for 10min, remove bubbles, place at 5℃ for 10h to gel, and obtain pre-loose crosslinked gel;

[0048] S4, placing the pre-loose cross-linked gel in a fixture and pre-stretching the length to 0%, and then immersing it in a 5wt% dilute sulfuric acid solution to react for 1 min to form an anisotropic cellulose hydrogel;

[0049] S5. The cellulose hydrogel is immersed in a 5wt% ammonium persulfate solution for 3 hours, then taken out, pyrrole is added, and polymerization growth is carried out at room temperature for 24 hours. The cellulose hydrogel is washed with water several times, and frozen at -20°C for 24 hours. The surface layer is removed by phase separation means, and the cellulose hydrogel is further immersed in the ammonium persulfate solution for 2 hours. The cellulose hydrogel is frozen at -20°C for 12 hours, and then taken out after freeze drying. The cellulose hydrogel is polymerized and grown for 4 hours at room temperature, and freeze dried to form an aerogel, i.e., a polypyrrole / cellulose gel with an anisotropic structure.

[0050] Example 2

[0051] Based on Example 1, the pre-stretching length is adjusted to 80%;

[0052] That is, the method for preparing the anisotropic polypyrrole / cellulose gel of this embodiment comprises the following specific steps:

[0053] S1. Weigh 7 g of sodium hydroxide and 12 g of urea, add into 81 mL of water, and prepare alkaline urea solution;

[0054] S2, weighing 6 g of microcrystalline cellulose, adding it to the above 10 mL of alkaline urea solution, ultrasonically treating it at 1000 rpm and 25° C. for 20 min, first freezing it at -20° C. for 12 h, taking it out, stirring it in an ice bath for 30 min, repeating the above freeze-thaw process 2-3 times to obtain a cellulose solution;

[0055] S3, take out 50g of cellulose solution, then add 1.6g of epichlorohydrin crosslinking agent, stir at -0℃, 1000rpm, for 4h, place in a centrifuge, centrifuge at 6000rpm for 10min, remove bubbles, place at 5℃ for 10h to gel, and obtain pre-loose crosslinked gel;

[0056] S4, placing the pre-loose cross-linked gel in a fixture and pre-stretching the length by 80%, and then immersing it in a 5wt% dilute sulfuric acid solution to react for 1 min to form an anisotropic cellulose hydrogel;

[0057] S5. The cellulose hydrogel is immersed in a 5wt% ammonium persulfate solution for 3 hours, then taken out, pyrrole is added, and polymerization growth is carried out at room temperature for 24 hours. The cellulose hydrogel is washed with water several times, and frozen at -20°C for 24 hours. The surface layer is removed by phase separation means, and the cellulose hydrogel is further immersed in the ammonium persulfate solution for 2 hours. The cellulose hydrogel is frozen at -20°C for 12 hours, and then taken out after freeze drying. The cellulose hydrogel is polymerized and grown for 4 hours at room temperature, and freeze dried to form an aerogel, i.e., a polypyrrole / cellulose gel with an anisotropic structure.

[0058] Example 3

[0059] Based on Example 1, the pre-stretching length is adjusted to 160%;

[0060] That is, the method for preparing the anisotropic polypyrrole / cellulose gel of this embodiment comprises the following specific steps:

[0061] S1. Weigh 7 g of sodium hydroxide and 12 g of urea, add into 81 mL of water, and prepare alkaline urea solution;

[0062] S2, weighing 6 g of microcrystalline cellulose, adding it to the above 20 mL of alkaline urea solution, ultrasonically treating it at 1000 rpm and 25° C. for 20 min, first freezing it at -20° C. for 12 h, taking it out, stirring it in an ice bath for 30 min, repeating the above freeze-thaw process 2-3 times to obtain a cellulose solution;

[0063] S3, take out 50g of cellulose solution, then add 1.6g of epichlorohydrin crosslinking agent, stir at 0℃, 1000rpm, for 4h, place in a centrifuge, centrifuge at 6000rpm for 10min, remove bubbles, place at 5℃ for 10h to gel, and obtain pre-loose crosslinked gel;

[0064] S4, placing the pre-loose cross-linked gel in a fixture and pre-stretching the length by 160%, and then immersing it in a 5wt% dilute sulfuric acid solution to react for 1 min to form an anisotropic cellulose hydrogel;

[0065] S5. The cellulose hydrogel is immersed in a 5wt% ammonium persulfate solution for 3 hours, then taken out, pyrrole is added, and polymerization growth is carried out at room temperature for 24 hours. The cellulose hydrogel is washed with water several times, and frozen at -20°C for 24 hours. The surface layer is removed by phase separation means, and the cellulose hydrogel is further immersed in the ammonium persulfate solution for 2 hours. The cellulose hydrogel is frozen at -20°C for 12 hours, and then taken out after freeze drying. The cellulose hydrogel is polymerized and grown for 4 hours at room temperature, and freeze dried to form an aerogel, i.e., a polypyrrole / cellulose gel with an anisotropic structure.

[0066] 1. The anisotropic polypyrrole / cellulose gel (MCC@PPy-160%) of Example 3 was analyzed by scanning electron microscopy, see Figure 1 ,from Figure 1 It can be seen that the polypyrrole / cellulose gel of Example 3 exhibits anisotropic structural characteristics, and the raised parts tend to be anisotropically parallel.

[0067] 2. The anisotropic polypyrrole / cellulose gel prepared in Example 3 was subjected to Fourier transform infrared spectroscopy analysis, see Figure 2 ,from Figure 2 It can be seen that if the cellulose gel without polypyrrole is stretched and oriented to 0%, 80% and 160%, the peak position of the functional group does not change, indicating that different degrees of orientation have no effect on the structure of cellulose. However, the peak position of the cellulose gel loaded with polypyrrole shows obvious polypyrrole characteristic peak position, indicating that the cellulose gel of Example 3 is successfully loaded with polypyrrole.

[0068] 3. Infrared thermal imaging analysis of the anisotropic polypyrrole / cellulose gel prepared in Examples 1-3, see Figure 3 ,from Figure 3 It can be seen that the heating rates of polypyrrole / cellulose gels with different degrees of orientation in Examples 1-3 are different, and the higher the degree of orientation, the faster the heating rate. In particular, the temperature of MCC@PPy-160% in Example 3 reached 66.8°C in 30 minutes, proving that there is enough heat to evaporate water during the photothermal evaporation process and improve the thermal management performance.

[0069] 4. For a description of the heating curves of the anisotropic polypyrrole / cellulose gels prepared in Examples 1-3, see Figure 4 ,from Figure 4 It can be seen that with the increase of time, the temperature of the anisotropic polypyrrole / cellulose gel of Examples 1-3 gradually increases. Within 300 s, the reaction temperature rise rate of Example 3 is greater than that of Example 1 and Example 2, indicating that MCC@PPy-160% of Example 3 has efficient photothermal conversion ability.

[0070] 5. The effect of water evaporation on the anisotropic polypyrrole / cellulose gel prepared in Examples 1-3 is studied, see Figure 5 ,from Figure 5 It can be seen that with the increase of orientation degree, the water evaporation rate increases, that is, the MCC@PPy-160% of Example 3 reaches 2.68 kg·m in 1 h. -2 evaporation rate.

[0071] 6. Verify the effect of the anisotropic polypyrrole / cellulose gel (MCC@PPy-160%) prepared in Example 3 on generating voltage under dark conditions, see Figure 6 ,from Figure 6 It can be seen that as the concentration of sodium chloride increases, the generated voltage gradually increases. This is due to the generation of streaming potential and the matching of the Debye radius. It can be seen from the figure that the maximum voltage reaches 0.7V at 0.1mol / L.

[0072] When in dark conditions, 0.1 mol / L sodium chloride has an effect on the voltage generated by the anisotropic polypyrrole / cellulose gel prepared in Example 1-3, see Figure 7 ,from Figure 7 It can be seen that as the degree of orientation increases, the voltage becomes larger and larger.

[0073] 7. Verify the effect of the anisotropic polypyrrole / cellulose gel (MCC@PPy-160%) prepared in Example 3 on generating voltage under light conditions, see Figure 8 ,from Figure 8 It can be seen that the maximum open circuit voltage exceeds 0.8V, and as the salt solution evaporates, the voltage can be output stably for 2000s. This is because the sample generates streaming potential and thermoelectric potential under light conditions, and the streaming potential is the main force to generate voltage, while the thermoelectric potential can amplify the difference in thermophoretic mobility between anions and cations.

[0074] 8. Verify the effect of the anisotropic polypyrrole / cellulose gel (MCC@PPy-160%) prepared in Example 3 on generating current under light conditions, see Fig. 9 ,from Fig. 9It can be seen that as the concentration of sodium chloride increases, the current is also increasing.

[0075] Comparative Example 1

[0076] The difference from Example 3 is that polypyrrole is not loaded, and the rest is the same as Example 3.

[0077] That is, the preparation method of the anisotropic cellulose gel of this comparative example specifically comprises the following steps:

[0078] S1. Weigh 7 g of sodium hydroxide and 12 g of urea, add into 81 mL of water, and prepare alkaline urea solution;

[0079] S2, weighing 6 g of microcrystalline cellulose, adding it to the above 15 mL of alkaline urea solution, ultrasonically treating it at 1000 rpm and 25° C. for 20 min, first freezing it at -20° C. for 12 h, taking it out, stirring it in an ice bath for 30 min, repeating the above freeze-thaw process 2-3 times to obtain a cellulose solution;

[0080] S3, take out 50g of cellulose solution, then add 1.6g of epichlorohydrin crosslinking agent, stir at -0℃, 1000rpm, for 4h, place in a centrifuge, centrifuge at 6000rpm for 10min, remove bubbles, place at 5℃ for 10h to gel, and obtain pre-loose crosslinked gel;

[0081] S4. The pre-loose cross-linked gel is placed in a fixture and pre-stretched to 160%, and then immersed in a 5wt% dilute sulfuric acid solution to react for 1 min to form an anisotropic cellulose hydrogel, which is freeze-dried to form an aerogel, i.e., an anisotropic polypyrrole / cellulose gel.

[0082] Comparative Example 2

[0083] The difference from Example 3 is that the formed polypyrrole / cellulose gel structure is a homogeneous structure, and the rest is consistent with Example 3.

[0084] 1. The effects of water evaporation on the samples of Example 3 and Comparative Example 1 were studied, see Fig.10 ,from Fig.10 It can be seen that the evaporation rate of the sample (MCC-160%) without polypyrrole loading in Comparative Example 1 is much lower than that of the sample (MCC@PPy-160%) loaded with polypyrrole in Example 3.

[0085] 2. Compare the voltage generation effects of the samples of Example 3 and Comparative Example 1, see Fig.11 ,from Fig.11 It can be seen that the sample of comparative example 1 without polypyrrole loading (MCC-160%) has almost no voltage. This is because the sample of comparative example itself has no conductivity and a double electric layer appears at the same time.

[0086] 3. The polypyrrole / cellulose gel structure of Comparative Example 2 is an isotropic structure, and its thermal management and low ion transmission capabilities are reduced. This is because the anisotropic structure has an ordered orientation structure compared to the isotropic structure, which makes the heat or ion transmission directional and reduces the disordered conduction of ions and heat.

[0087] Application Examples

[0088] The total voltage of the four MCC@PPy-160% of Example 3 was tested in series, see Fig.12 ,from Fig.12 It can be seen that four 2cm×1cm samples can generate a voltage of nearly 3V after being connected in series, and four MCC@PPy-160% samples connected in series successfully light up a small light bulb, providing a broader theoretical basis for subsequent applications.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing anisotropic polypyrrole / cellulose gel, characterized in that: The specific steps include: S1, adding sodium hydroxide and urea into water to obtain an alkaline urea solution; S2, adding microcrystalline cellulose to the alkaline urea solution of S1, ultrasonically treating, and repeatedly freezing and thawing to obtain a cellulose solution; S3, adding epichlorohydrin crosslinking agent to the cellulose solution in S2, stirring, centrifuging, and gelling at low temperature to obtain a pre-loose crosslinked gel; S4, pre-stretching the pre-loose cross-linked gel of S3 to a length of 0%-160% and then immersing it in a dilute sulfuric acid solution to react, thereby forming anisotropic cellulose hydrogels with different degrees of orientation; S5. Soak the cellulose hydrogel of S4 in an ammonium persulfate solution, take it out, add pyrrole for polymerization growth, and freeze-dry to form an aerogel, i.e., a polypyrrole / cellulose gel with an anisotropic structure.

2. The method for preparing anisotropic polypyrrole / cellulose gel according to claim 1, characterized in that: In step S1, the mass ratio of the sodium hydroxide to urea is 1:1.5-2.5; the solid-liquid ratio of the sodium hydroxide to water is 1:11-13 g / mL.

3. The method for preparing anisotropic polypyrrole / cellulose gel according to claim 1, characterized in that: In step S2, the solid-liquid ratio of the microcrystalline cellulose to the alkaline urea solution is 1:10-20 g / mL; and the ultrasonic treatment is performed at 500-1000 rpm and 25-30° C. for 10-20 min.

4. The method for preparing anisotropic polypyrrole / cellulose gel according to claim 1, characterized in that: In step S2, the repeated freezing and thawing is specifically as follows: first freezing at -20°C for 12-14 hours, taking out, stirring in an ice bath for 30-60 minutes, and repeating the above process 2-3 times.

5. The method for preparing anisotropic polypyrrole / cellulose gel according to claim 1, characterized in that: In step S3, the mass ratio of the epichlorohydrin crosslinking agent to the cellulose solution is 1.5-1.6:50; the stirring treatment is carried out at a temperature of -5 to 0°C, a rotation speed of 1000-1500 rpm, and a time of 2-4 hours.

6. The method for preparing anisotropic polypyrrole / cellulose gel according to claim 1, characterized in that: In step S3, the low temperature gelling is carried out by placing the mixture at 5-10° C. for 8-10 hours.

7. The method for preparing anisotropic polypyrrole / cellulose gel according to claim 1, characterized in that: In step S4, the concentration of the dilute sulfuric acid solution is 5-8 wt %; and the reaction time is 1-2 min.

8. The method for preparing anisotropic polypyrrole / cellulose gel according to claim 1, characterized in that: In step S5, the concentration of the ammonium persulfate solution is 2-10wt%; the immersion time is 1-3h; the specific process of the pyrrole polymerization growth is: firstly polymerize and grow at room temperature for 20-24h, wash with water, freeze at -20°C for 12-24h, remove the surface layer, continue to immerse in the ammonium persulfate solution for 1-2h, freeze at -20°C for 12-24h, take out after freeze drying, and polymerize and grow at room temperature for 4-6h.

9. A polypyrrole / cellulose gel with an anisotropic structure, prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the anisotropic polypyrrole / cellulose gel according to claim 9 in the field of solar seawater desalination and electric power utilization.

Citation Information

Patent Citations

  • Preparation method of ultra-high-strength anisotropic hydrogel containing cellulose nano-whiskers

    CN108409997A

  • Biomass nanocellulose / polypyrrole composite aerogel, and preparation method and application thereof

    CN111518309A